DNA methylation of genes in adipose tissue. - Pinnick, K; Karpe, F (2011)
Body fat distribution plays an important role in determining metabolic health. Whereas central obesity is closely associated with the development of CVD and type 2 diabetes, lower body fat appears to be protective and is paradoxically associated with improved metabolic and cardiovascular profiles. Physiological studies have demonstrated that fatty acid handling differs between white adipose tissue depots, with lower body white adipose tissue acting as a more efficient site for long-term lipid storage. The regulatory mechanisms governing these regional differences in function remain to be elucidated. Although the local microenvironment is likely to be a contributing factor, recent findings point towards the tissues being intrinsically distinct at the level of the adipocyte precursor cells (pre-adipocytes). The multi-potent pre-adipocytes are capable of generating cells of the mesenchymal lineage, including adipocytes. Regional differences in the adipogenic and replicative potential of these cells, as well as metabolic and biochemical activity, have been reported. Intriguingly, the genetic and metabolic characteristics of these cells can be retained through multiple generations when the cells are cultured in vitro. The rapidly emerging field of epigenetics may hold the key for explaining regional differences in white adipose tissue gene expression and function. Epigenetics describes the regulation of gene expression that occurs independently of changes in DNA sequence, for instance, DNA methylation or histone protein modification. In this review, we will discuss the contribution of DNA methylation to the determination of cells of adipogenic fate as well as the role DNA methylation may play during adipocyte terminal differentiation.